Control of Metal Nanocrystal Size Reveals Metal-Support Interface Role for Ceria Catalysts - Cargnello, Matteo; Doan-Nguyen, Vicky V. T.; Gordon, Thomas R.; Diaz, Rosa E.; Stach, Eric A.; Gorte, Raymond J.; Fornasiero, Paolo; Murray, Christopher B. (Science (American Association for the Advancement of Science), 2013)
Interactions between ceria (CeO 2 ) and supported metals greatly enhance rates for a number of important reactions. However, direct relationships between structure and function in these catalysts have been difficult to extract because the samples studied either were heterogeneous or were model systems dissimilar to working catalysts. We report rate measurements on samples in which the length of the ceria-metal interface was tailored by the use of monodisperse nickel, palladium, and platinum nanocrystals. We found that carbon monoxide oxidation in ceria-based catalysts is greatly enhanced at the ceria-metal interface sites for a range of group VIII metal catalysts, clarifying the pivotal role played by the support.